2001
DOI: 10.1177/089124301015002007
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Race and Gender on Student Self-Reports of Sexual Harassment by College Professors

Abstract: A survey of 525 undergraduates found that 40 percent of the women and 28.7 percent of the men had been sexually harassed by a college professor or instructor. Most incidents were gender harassment. While women reported significantly more gender harassment than did men, there were no gender differences in the frequency of unwanted sexual attention or sexual coercion. At least one incident of sexual harassment by a professor was experienced by 30 percent of the Blacks, 30 percent of the Hispanics, 33 percent of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
89
1
12

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 26 publications
2
89
1
12
Order By: Relevance
“…The Vignette Tests are based on 4 pictures of young men that are accompanied by short texts that describe the men, particularly in terms of their attractiveness and their attitudes towards women. Two of the 4 pictures and descriptions portray young men who behave violently (Vignettes 1 and 3) and whose attitudes are considered in the literature to exemplify violence against women (Banyard et al, 2005;Fisher, Cullen & Turner, 1999;Gross et al, 2006;Kalof et al, 2001). In contrast, the other pictures (Vignettes 2 and 4) portray men who are not violent or sexist and whose attitudes are linked with kindness.…”
Section: Instrument and Interventionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Vignette Tests are based on 4 pictures of young men that are accompanied by short texts that describe the men, particularly in terms of their attractiveness and their attitudes towards women. Two of the 4 pictures and descriptions portray young men who behave violently (Vignettes 1 and 3) and whose attitudes are considered in the literature to exemplify violence against women (Banyard et al, 2005;Fisher, Cullen & Turner, 1999;Gross et al, 2006;Kalof et al, 2001). In contrast, the other pictures (Vignettes 2 and 4) portray men who are not violent or sexist and whose attitudes are linked with kindness.…”
Section: Instrument and Interventionmentioning
confidence: 99%
“…The survey presented pictures of four men accompanied by a short explanation of their characters. The explanations of man 1 and man 3 included sentences that describe behaviours characterized as gender violence in previous international surveys (Banyard et al, 2005;Fisher, Cullen, & Turner, 1999;Gross et al, 2006;Kalof et al, 2001). The descriptions of man 2 and man 4 only included non-sexist behaviours.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dziech (2003) reported that university faculty members have victimized approximately 30% of undergraduate females and 40% of female graduate students, whereas 90% of undergraduate females reported unwanted behavior from their male peers. However, these estimates may not accurately represent the true rate of victimization because of the general consensus that individuals of differing races and genders perceive, label, and report sexual harassment differently (Birdeau et al, 2005;Fitzgerald & Ormerod, 1991;Ivy & Hamlet, 1996;Kalof, Eby, Matheson, & Kroska, 2001;Kelley & Parsons, 2000;Magley & Shupe, 2005;Shelton & Chavous, 1999). For example, research suggests that sexual harassment is more likely to occur among certain populations including females, graduate students, women in nontraditional fields, minority females, disabled persons, divorced women, young and naïve females, persons who were sexually abused, and homosexuals (Cortina et al, 1998;Dziech, 2003;Kalof et al, 2001;Paludi, 1997;Russell & Oswald, 2001).…”
Section: Literature Overviewmentioning
confidence: 99%
“…Sexual harassment has been well documented within a variety of settings, including the sales industry (Collinson & Collinson, 1996), service sector jobs (Folgero & Fjeldstad, 1995;Giuffre & Williams, 1994), and academia (Benson & Thomson, 1982;Kalof, Eby, Matheson, & Kroska, 2001). Women in traditionally male occupations face more regular and severe forms of workplace harassment than those engaged in female-typed work (Eisenberg, 2001;Fitzgerald, Drasgow, Hulin, Gefland, & Magley, 1997;Mansfield, Koch, Henderson, Vicary, Cohn, & Young, 1991;Pierce, 2004).…”
Section: Conceptualizing Harassment and Social Classmentioning
confidence: 99%